Childhood Mental Disorders and Risk of Schizophrenia - Liang, Wenbin; Chikritzhs, Tanya (Science Publications, 2012)
Problem statement: Schizophrenia is one of the most serious forms of mental diseases, but the etiology of schizophrenia is still not well understood. Investigations are required to gain better understanding of the pre-onset course of schizophrenia. Approach: This study was a population-based birth-cohort study of males born between 1980 and 1984 in Western Australia (WA). Males were identified using birth registry records and followed-up until December 31st, 2009 or death using linked health data available through the Western Australian Data Linkage System (WADLS). Results: Children who developed a mental disorder before the age of 12 yrs had about at twice the risk of developing schizophrenia compared to those without a diagnosis. Increased risks appeared to be greatest for specific delays in development and hyperkinetic syndrome of childhood. Conclusion: Children with childhood mental disorders are at higher risk of being diagnosed with schizophrenia later in life. These findings provide further evidence to support the hypothesis that schizophrenia is a neurodevelopmental disorder.